A phenomenological study of primary caregivers of patients living with schizophrenia in Gauteng Province, South Africa - Nopfumbada, Tshilidzi Tracy (My University, 2019)
The study sought to explore and describe the lived experiences of caregivers involved in support groups whilst caring for a family member diagnosed schizophrenia in Johannesburg South, Gauteng province. A qualitative study was conducted among primary caregivers of family members diagnosed with schizophrenia and involved in support groups. Members were selected using purposive sampling and ten participants were interviewed (eight parents and two siblings of diagnosed family members). Data were collected using semi-structured interviews and analysed using interpretive phenomenological analysis (IPA). Common themes regarding the experience of caring for a family member diagnosed with schizophrenia were clearly delineated. Findings of the study revealed that the participants experienced psychosocial, emotional, and economic challenges in caring for their relatives diagnosed with schizophrenia. The findings point to problems such as psychological distress, extensive worry, subjective burden and significance of support in caring for ill family members. Findings also highlight challenges such as financial constraints and cultural factors which negatively impact the quality of caregiving for the participants’ ill relatives. The study further revealed the coping mechanisms that caregivers adopt to cope with the difficulties of caring for their schizophrenic family members. Religion and support groups were some of mechanisms a majority of participants found to be helpful for them in coping. The present study found that family members involved in the group program demonstrated improved family communication, greater confidence in their ability to help their loved ones, reduced burden and improved subjective quality of life.
Thesis (M. A. (Clinical Psychology)) -- University of Limpopo, 2019
Keywords: Caregivers; Schizophrenia; Gauteng Province; Schizophrenics -- Family relationships; Caregivers -- Family relationships; Schizophrenics -- Home care; Schizophrenia -- Physiological aspects